Reading the Psalms as a Book - Curtis, Adrian H. W. (Journal of Semitic studies, 2002)
Reading the Psalms as a Book NormanWhybray (JSOT Supplement Series 222). Sheffield Academic PressSheffield 19661371‐85075‐622‐8 , 1University of Manchester